2017
DOI: 10.1080/03610918.2017.1307398
|View full text |Cite
|
Sign up to set email alerts
|

Optimal inference for Simon's two-stage design with over or under enrollment at the second stage

Abstract: Simon’s two-stage designs are widely used in clinical trials to assess the activity of a new treatment. In practice, it is often the case that the second stage sample size is different from the planned one. For this reason, the critical value for the second stage is no longer valid for statistical inference. Existing approaches for making statistical inference are either based on asymptotic methods or not optimal. We propose an approach to maximize the power of the study while maintaining the type I error rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…e objective of this manuscript is to conduct extensive simulation studies to compare the existing correlations for repeated measures with regard to the average of correlation and the mean squared error (MSE) and identify the correlation method that has the best performance to be used in practice. In addition to the parameter of interest (correlation for repeated measures), there are several nuisance parameters in the variance-covariance matrix: variances, correlations within each outcome, and correlation between outcomes from different visits [17][18][19][20]. It is computationally intensive for these comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…e objective of this manuscript is to conduct extensive simulation studies to compare the existing correlations for repeated measures with regard to the average of correlation and the mean squared error (MSE) and identify the correlation method that has the best performance to be used in practice. In addition to the parameter of interest (correlation for repeated measures), there are several nuisance parameters in the variance-covariance matrix: variances, correlations within each outcome, and correlation between outcomes from different visits [17][18][19][20]. It is computationally intensive for these comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…An additional critical response value was introduced for the first stage termination due to efficacy, and they developed a statistical software package to compute these designs [2]. Recently, other modified Simon’s designs, such as adaptive two-stage designs [37], have been developed to improve the flexibility and efficiency of a trial by allowing the second stage sample size to be changed as the observed first stage responses.…”
Section: Introductionmentioning
confidence: 99%